"FILLING IN", THOUGHT EXPERIMENTS AND INTUITIONS. (25th July 2016) - Shaffer, Michael J.
Abstract: Recently Timothy Williamson has argued that characterizations of the standard (i.e. intuition-based) philosophical practice of philosophical analysis are misguided because of the erroneous manner in which this practice has been understood. In doing so he implies that experimental critiques of the reliability of intuition are based on this misunderstanding of philosophical methodology and so have little or no bearing on actual philosophical practice or results. His main point is that the orthodox understanding of philosophical methodology is incorrect in that it treats philosophical thought experiments in such a way that they can be "filled in" in various ways that undermines their use as counter-examples and that intuition plays no substantial role in philosophical practice when we properly understand that methodology as a result of the possibility of such filling in. In this paper Williamson's claim that philosophical thought experiments cases can be legitimately filled in this way will be challenged and it will be shown that the experimental critique of the intuition-based methods involved a serious issue.